The sensitive Amnesia Light and Brief Assessment (ALBA) is a valid 3-min test of 4 tasks indicative of mild cognitive deficits - A. Bartos; S. Diondet (Neurología (English Edition))
Background and purpose: We report the development and validation of a unique, easily administered, but cognitively demanding 3-min test that does not require aids and can detect mild cognitive deficits (MCD). Methods: The innovative Amnesia Light and Brief Assessment (ALBA) consists of 4 tasks: encoding the 6-word sentence “Indian summer brings first morning frost,” sequential demonstration of 6 gestures and their immediate recall, and final recall of the original sentence. The memory ALBA score is the sum of all correctly recalled sentence words and gestures. The ALBA was performed in 590 persons older than 50 years, including 60 individuals who completed a neuropsychological battery, equally divided into patients with MCD (Montreal Cognitive Assessment [MoCA] score of 21 ± 3 points) and matched cognitively normal (CN) individuals (MoCA of 27 ± 2). Results: Compared to CN individuals, the patients with MCD recalled fewer correct sentence words (median, 5 vs 2) and gestures (4 vs 3), and had lower memory ALBA scores (10 vs 6) (all comparisons, P < .00001). The cut-off point for the memory ALBA score was ≤8, with 90% sensitivity, 77% specificity, and an AUC of 0.90. Memory ALBA score correlated significantly with all neuropsychological tests except the Digit Span forward. The ALBA was minimally associated with education and age in the normative sample. Conclusions: The novel and efficient ALBA test was confirmed to have high discriminant and convergent validity, even in patients with mild cognitive deficits. The ALBA is an ultra-brief and universal cognitive test suitable for assessing cognitive impairment, dementia, and other conditions. It can easily be adapted to other cultures and administered under various conditions and settings in clinical practice and research. Resumen: Antecedentes y propósito: Desarrollo y validación de una prueba de 3 min única, fácil de administrar, pero cognitivamente exigente que no requiere ayudas y puede detectar déficits cognitivos leves. Métodos: La innovadora evaluación breve y ligera de amnesia (ALBA) consta de 4 tareas: codificación de una oración de 6 palabras «Indian Summer Brings First Morning Frost», demostración secuencial de 6 gestos y su recuerdo inmediato, y recuerdo final de la oración original. La puntuación ALBA es una suma de palabras de una frase y gestos recordados correctamente. El ALBA se realizó en 590 personas mayores, incluidas 60 personas con una batería neuropsicológica dividida equitativamente en pacientes con déficit cognitivo leve (MCD) (evaluación cognitiva de Montreal: 21 ± 3 puntos) e individuos cognitivamente normales (CN) emparejados (MoCA 27 ± 2). Resultados: En comparación con CN, los pacientes con MCD recordaron menos palabras de oraciones correctas (mediana de 5 frente a 2), gestos (4 frente a 3) y puntuaciones ALBA más bajas (10 frente a 6) (todos p < 0,00001). El punto de corte de la puntuación ALBA fue ≤ 8 con una sensibilidad del 90%, una especificidad del 77% y un AUC de 0,90. Se correlacionó significativamente con todas las pruebas neuropsicológicas excepto con Digit Span Forward. El ALBA se asoció mínimamente con la educación y la edad en la muestra normativa. Conclusiones: Se confirmó que la nueva y eficiente prueba ALBA tiene una alta validez discriminante y convergente incluso en aquellos con déficits cognitivos leves. El ALBA es una prueba cognitiva ultrabreve y universal adecuada para evaluar el deterioro cognitivo, la demencia y otras condiciones. Puede adaptarse fácilmente a otras culturas y administrarse en diversas condiciones y entornos en la práctica clínica y la investigación.